Derived-Term Automata of Multitape Expressions with Composition - A. Demaille (Scientific Annals of Computer Science)
Rational expressions are powerful tools to define automata, but often restricted to single-tape automata. Our goal is to unleash their expressive power for transducers, and more generally, any multitape automaton; for instance